The Genesis and Exodus of Vascular Plant DOM from an Oak Woodland Landscape - Hernes, Peter J.; Spencer, Robert G. M.; Dyda, Rachael Y.; O'Geen, Anthony T.; Dahlgren, Randy A. (Frontiers in Earth Science, 2017)
Evaluating the collective impact of small source inputs to larger rivers is a constant challenge in riverine biogeochemistry. In this study, we investigated the generation of dissolved organic matter (DOM) in a small oak woodland catchment in the foothills of northern California, the subsequent transformation in lignin biomarkers and chromophoric DOM (CDOM) parameters during transport through the landscape to an exporting stream, and finally the overall compositional impact on the larger receiving stream and river. Our study included a natural leaching experiment in which precipitation passing through oak, pine, and grass litter and duff samples was collected after each of a series of storms. Also included were soil trench samples to capture subsurface flow, stream samples along with point-source reservoir inputs, and samples of canopy throughfall, stemflow, and gopher hole (bypass) flow. The litter/duff leaching study demonstrated changing DOM fractionation patterns throughout the season, as evidenced by changing lignin compositions in the leachates with each successive storm. This adds a necessary seasonal component to interpreting lignin compositions in streams, as the source signatures are constantly changing. Released DOM from leaching was modified extensively during transit through the subsurface to the stream, with preferential increases in aromaticity as evidenced by increases in carbon-normalized absorbance at 254 nm, yet preferential decreases in lignin phenols, as evidence by carbon-normalized lignin yields in the headwater stream that was less than half that of the litter/duff leachates. Our extensive number of lignin measurements for source materials reveals a much more complex perspective on using lignin as a source indicator, as many riverine values for syringyl:vanillyl and cinnamyl:vanillyl ratios that have previously been interpreted as degraded lignin signatures are also possible as unmodified source signatures. Finally, this study demonstrated that the impact of numerous small headwater streams can significantly overprint the DOM signatures of much larger rivers over relatively short distances spanning several to tens of kilometers. This finding in particular challenges the assumption that river studies can be adequately conducted by focusing only on the main tributaries.